PENERAPAN SUPERVISI AKADEMIS PENGAWAS SEKOLAH UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU NON KEPENDIDIKAN SDN 003 BAGAN HULU KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Zuraida Zuraida (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This study is a school action research that aims to improve pedagogic competence of non-educational teachersSDN 003 Bagan Hulu through Academic Supervision. This research was conducted in SDN 003 Bagan Hulu,this research was conducted in two cycles with four stages: planning, implementation, observation, andreflection. In this study researchers only focus on the ability of teachers in preparing lesson planning. The resultof research stated that after applied by academic supervision by supervisor, teacher's ability in making learningplan is increasing. This is seen from the initial scores of indicators of the indicators of learning objectives toobtain data of 40% in the first cycle has increased with a score of 60% and in the second cycle has increasedagain up to 70%. In the indicator of the determination of the material / subject matter at the initial scoreobtained a score of 65%, in the first cycle increased up to 70%, and in the second cycle increased to 80%. In theindicator of the use of learning media at the initial score of 40%, in the first cycle increased up to 60%, and inthe second cycle increased to 80%. In the indicator of strategy selection and learning method in the initial scoreof 40%, in the first cycle increased up to 60%, and in the second cycle increased up to 75%. And on indicatorcomponent of learning evaluation planning at initial score get 40%, in the first cycle has increased up to 60%,and in cycle II have increase until 70%.